Carbohydrate restricted recovery from long term endurance exercise does not affect gene responses involved in mitochondrial biogenesis in highly trained athletes. - Jensen, L.; Gejl, K. D.; Ørtenblad, N.; Nielsen, J. L.; Bech R. D.; Nygaard, T.; Sahlin, K.; Frandsen, U. (Physiological Reports, 2015)
The aim was to determine if the metabolic adaptations, particularly PGC-1a and downstream metabolic genes were affected by restricting CHO following an endurance exercise bout in trained endurance athletes. A second aim was to compare baseline expression level of these genes to untrained. Elite endurance athletes (VO2max 66 ± 2 mL·kg(-1)·min(-1), n = 15) completed 4 h cycling at ~56% VO2max. During the first 4 h recovery subjects were provided with either CHO or only H2O and thereafter both groups received CHO. Muscle biopsies were collected before, after, and 4 and 24 h after exercise. Also, resting biopsies were collected from untrained subjects (n = 8). Exercise decreased glycogen by 67.7 ± 4.0% (from 699 ± 26.1 to 239 ± 29.5 mmol·kg(-1)·dw(-1)) with no difference between groups. Whereas 4 h of recovery with CHO partly replenished glycogen, the H2O group remained at post exercise level; nevertheless, the gene expression was not different between groups. Glycogen and most gene expression levels returned to baseline by 24 h in both CHO and H2O. Baseline mRNA expression of NRF-1, COX-IV, GLUT4 and PPAR-a gene targets were higher in trained compared to untrained. Additionally, the proportion of type I muscle fibers positively correlated with baseline mRNA for PGC-1a, TFAM, NRF-1, COX-IV, PPAR-a, and GLUT4 for both trained and untrained. CHO restriction during recovery from glycogen depleting exercise does not improve the mRNA response of markers of mitochondrial biogenesis. Further, baseline gene expression of key metabolic pathways is higher in trained than untrained.